Perceived Social Support and Associated Factors Among Community-Dwelling Older Adults With Frailty and Pre-frailty in Hangzhou, China - Fang, Juan; Ren, Jianping; Ren, Lixian; Qiu, Xiantao; Yuan, Shuang; Wang, Wenting; Wang, Jinjing (Frontiers in Psychiatry, 2022)
Objectives: The present study aimed to explore the social support among community-dwelling older adults with frailty and pre-frailty and to ascertain associated factors. Methods: The frailty status of the participant was assessed via the Chinese FRAIL Scale. The dependent variable, level of social support, was evaluated using the Social Support Rating Scale (range: 12 to 66). This study explored the influencing factors from three aspects containing sociodemographic characteristics, family environment, and community environment. Independent-sample t-test, Analysis of Variance, and multiple linear regression analyses were conducted to examine determinants of social support. Results: There were significant statistical differences in overall social support between non-frail, pre-frail, and frail participants [with 38.01 (SD=6.48) vs, 33.62 (SD=6.25) vs, and 30.50 (SD=6.68), F= 62.157, p＜0.001]. Older adults with frailty and pre-frailty who were single would have lower levels of overall social support. In the pre-frail group, living alone was associated with lower overall social support. In contrast, the relationship with children and the availability of recreational activities were associated factors for the frail group. Conclusions: The level of social support among frail and pre-frail community-dwelling older adults was lower than the robust older adults and influenced by different factors according to the frailty category, which suggests taking targeted measures for social support improvement.